A global pandemic and a wildcat strike: How COVID-19 and civil unrest could impact the NBA`s labor relations - Herbert, B. A. (DePaul Journal of Sports Law, 2021)
The future of the NBA`s labor relations could be significantly impacted by the COVID-19 pandemic and the recent civil unrest around the country. The current NBA collective bargaining agreement was approved in 2016. In the four seasons following its approval, both owners and players were seemingly pleased with the general state of the league. The NBA`s annual revenue ballooned from $5.2 billion in 2016 to $8.8 billion in 2019, and there were few reports of any significant tension between owners and the Players Association. However, 2020 threw two wrenches that may crucially affect both the immediate and long-term relationship between owners and players: COVID-19 and the civil unrest around the country.